Computer fundamentals: for everyone interested in computers - Oka, Milind M (Everest Pub. House, 2010)
Computer fundamentals: for everyone interested in computers / Oka, Milind M.. -- Pune: Everest Pub. House, 2010 004 Ok41e15 15th ed. No. of Copies : 1